Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V SD Inpres 5/81 Bajoe Kabupaten Bone - Sudirman, Sudirman; Kadir, Abd; Fitriani, Fitriani (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2026)
This study aims to determine whether applying the problem-based learning model can improve science learning outcomes for Year 5 students at SD Inpres 5/81 Bajoe in the Bone Regency. The research design comprises two cycles of classroom action research. All 29 fifth-grade students and their teacher participated in the study. Data collection techniques included observations and learning outcome tests. Data analysis involved data reduction, presentation, and conclusion. The results showed that the teacher's management of learning activities improved from cycle I to cycle II. This was demonstrated by the more optimal and systematic implementation of the problem-based learning steps. Student activity also increased. This was evident in their increased involvement in discussions, problem-solving, and group presentations. These improvements impacted student learning outcomes. In Cycle I, 21 out of 29 students (73%) achieved mastery, achieving an average score of 71.1. In Cycle II, this increased to 25 students (82%), achieving an average score of 79.1. Based on these results, it can be concluded that the problem-based learning model effectively improves the learning outcomes of Grade V students in IPAS.